Honey price estimation for the future in Turkey; example of 2019-2020 - Cevrimli, Mustafa Bahadir; Arikan, Mehmet Saltuk; Tekindal, Mustafa Agah (Ankara Univ, 2020)
The purpose of the present study is to develop models for the time series data of honey prices in Turkey between 1998 and 2018 using Box-Jenkins and Winter's Exponential Smoothing methods and to evaluate the TRY- and US$-denominated forecasts made using such models for 2019-2020. The method employed to analyse the time series data is the Seasonal Auto Regressive Integrated Moving Average (SARIMA). The most suitable model to forecast the honey prices was found to be SARIMA (2,1,2)(1,0, 1) for TRY-denominated prices and SARIMA (0,1,3)(0,0,0) for US$-denominated prices. It was forecast that the average price of 1 kg of honey would be 49.08 TRY/6.15 US$ at the end of 2020. Since the study will provide beekeepers with information on future prices, it will help them better plan their production activities. The price forecasts in this study will be useful for producers and those involved in sale of honey with respect to prediction of how the honey prices will change in the years to come.
Türkiye’de bal fiyatlarının geleceğe yönelik kestirimi; 2019-2020 örneği
Keywords: Forecasting; honey; time series; Turkey